A new species of Centaurea sect. Cynaroides (Asteraceae, Cardueae–Centaureinae) from Iran - Negaresh, Kazem; Yousefi, Zohreh (Phytotaxa, 2025)
Centaurea saeidii Negaresh, a new species of C. sect. Cynaroides from the Kermanshah Province of W Iran, is described and illustrated. Diagnostic morphological characters of this and closely related taxa are presented and discussed. The ecology and conservation status of the new species are discussed. The geographic distributions of the new species and closely related species are also presented and mapped. In addition, a taxonomic key of C. saeidii and closely related taxa is provided.